2014
DOI: 10.1007/s12155-014-9546-1
|View full text |Cite
|
Sign up to set email alerts
|

Estimates of Biomass Yield for Perennial Bioenergy Grasses in the USA

Abstract: Perennial grasses, such as switchgrass (Panicum viragatum) and Miscanthus (Miscanthus × giganteus), are potential choices for biomass feedstocks with low-input and high dry matter yield per hectare in the USA and Europe.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
53
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(54 citation statements)
references
References 61 publications
(95 reference statements)
1
53
0
Order By: Relevance
“…Previous research has already led to the design of best management practices for many warm-season grasses (Mitchell, 2013) where many of those studies, either field-based or modeling, have looked at crop comparisons across locations, years, and/or fertilizer regimes (Lee, Mitchell, Heaton, Zumpf, & Lee, 2018;Song, Jain, Landuyt, Kheshgi, & Khanna, 2014;Wang, Lebaauer, & Dietze, 2010). The review of Wullschleger, Davis, Borsuk, Gunderson, and Lynd (2010), for example, suggested that 100 kg N/ha could be considered an optimum for both upland and lowland switchgrass ecotypes.…”
Section: Introductionmentioning
confidence: 99%
“…Previous research has already led to the design of best management practices for many warm-season grasses (Mitchell, 2013) where many of those studies, either field-based or modeling, have looked at crop comparisons across locations, years, and/or fertilizer regimes (Lee, Mitchell, Heaton, Zumpf, & Lee, 2018;Song, Jain, Landuyt, Kheshgi, & Khanna, 2014;Wang, Lebaauer, & Dietze, 2010). The review of Wullschleger, Davis, Borsuk, Gunderson, and Lynd (2010), for example, suggested that 100 kg N/ha could be considered an optimum for both upland and lowland switchgrass ecotypes.…”
Section: Introductionmentioning
confidence: 99%
“…Song et al . () used the mechanistic Integrated Science Assessment Model (ISAM) to estimate biomass yield potential in the eastern United States for Miscanthus, as well as an upland switchgrass cultivar (Cave‐in‐Rock) and a lowland switchgrass cultivar (Alamo) at coarse (0.5°) resolution. Yield patterns are similar to those of PRISM‐ELM in the major crop production areas of the United States, but production declines to zero north of the boundaries of USDA plant hardiness zones: zone 4 for Miscanthus, zone 3 for upland switchgrass, and zone 5 for lowland switchgrass.…”
Section: Discussionmentioning
confidence: 99%
“…PRISM‐ELM was designed to answer a basic question: How do climate and soil characteristics affect the spatial suitability and long‐term production patterns of a given crop? It draws from both empirical and mechanistic approaches and therefore falls into a hybrid category that is becoming more powerful as high‐quality climate, remote sensing, land use, and soils data become available (Song et al ., ; Wightman et al ., ; Richter et al ., ). It employs a simple water balance model to simulate the correspondence, or lack thereof, between water availability (based on precipitation and soil moisture) and growing season timing (based on a temperature response curve).…”
Section: Introductionmentioning
confidence: 99%
“…The biophysical potential to grow bioenergy grasses varies with time and space due to changes in environmental conditions (Song et al, 2015). Plants need a minimum as well as a maximum offer from the climate in order to satisfy its physiological requirements.…”
Section: The Agroclimatic Zoningmentioning
confidence: 99%